PO 35 - ANESTESIA NA FRATURA DO COLO DO FÉMUR - UMA AUDITORIA CLÍNICA - Sancha Andrade Oliveira Costa Santos1,; Helena Maria Ferreira da Silva1,; Joaquim Maria Rafael de Borba1,; Rui Freitas Mendonça Correia Silva1,; António Armando Furtado Paiva1,; Cecília Gomes Pinto Amarante Dias1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.